Formasi Identitas Pemuda Ojek Online dalam Risiko Ekonomi Politik Platform Digital - Ardy Rustu Irawan; Farhan Hasinul Amri; Febriyanto Hermawan; Lukman Hakim Alfaridzi (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
The phenomenon of online ojek as part of the platform-based economy has grown rapidly, especially in Indonesia. This job is in high demand by youth as an alternative job that offers flexibility. However, behind the benefits offered, this profession also carries economic, social, and political risks. This article aims to examine the identity formation of youth working as online ojek drivers in the context of political-economic risks that arise in digital platforms, using Ulrich Beck's Risk Society Theory. In the risk society, uncertainty and dependence on systems controlled by digital platforms are the main factors that shape the social identity of the drivers. This research finds that the identity of online ojek youth is formed through interactions with digital platforms that prioritize efficiency and profitability, as well as with the risks they face every day in working under systemic uncertainty.